Palatal assibilation before [w]? The case of Armenian, Saka, and Luwian - Hans Henrich Hock (Anuario del Seminario de Filología Vasca "Julio de Urquijo")
Three branches of Indo-European —Luwian, Armenian, and East Iranian (Khotanese) Saka— seem have undergone asssibilation of PIE palatal-prevelar stops before [w], a development contrasting with the general outcome of these stops in Armenian and Saka, and with their apparent outcome before [- front] vocalic segments in Luwian. So far, no principled phonetic or phonological explanations for this behavior have been proposed. I show that the developments in Saka and Armenican can be accounted for in terms of a crosslinguistic tendency for the high-vocalic labiovelar glide w, whether full segment w or nonsegmental offglide w, to assimilate to a following y or front vowel by becoming labiopalatal segmental ɥ or offglide ɥ, which following a common trend is unrounded to y or y and then palatalizes and assibilates the preceding stop. This account is not applicable to Luwian for which a general assimilation of palatal-prevelar before non-low vowels seems the best solution. The similarity between Armenian and Saka on one hand and Luwian on the other, thus, is accidental, and we must conclude that similar outcomes can be produced by very different historical developments.